Metabolic Engineering of Shikimic Acid-Producing Corynebacterium glutamicum From Glucose and Cellobiose Retaining Its Phosphotransferase System Function and Pyruvate Kinase Activities - Sato, Naoki; Kishida, Mayumi; Nakano, Mariko; Hirata, Yuuki; Tanaka, Tsutomu (Frontiers in Bioengineering and Biotechnology, 2020)
The production of aromatic compounds by microbial production is a promising and sustainable approach for producing biomolecules for various applications. We describe the metabolic engineering of Corynebacterium glutamicum to increase its production of shikimic acid. Shikimic acid and its precursor-consuming pathways were blocked by the deletion of the shikimate kinase, 3-dehydroshikimate dehydratase, shikimate dehydratase, and dihydroxyacetone phosphate phosphatase genes. Plasmid-based expression of shikimate pathway genes revealed that 3-deoxy-D-arabino-heptulosonate 7-phosphate (DAHP) synthase, encoded by aroG, and DHQ synthase, encoded by aroB, are key enzymes for shikimic acid production in C. glutamicum. We constructed a C. glutamicum strain with aroG, aroB and aroE3 integrated. This strain produced 13.1 g/L of shikimic acid from 50 g/L of glucose, a yield of 0.26 g-shikimic acid/g-glucose, and retained both its phosphotransferase system and its pyruvate kinase activity. We also endowed β-glucosidase secreting ability to this strain. When cellobiose was used as a carbon source, the strain produced shikimic acid at 13.8 g/L with the yield of 0.25 g-shikimic acid/g-glucose (1 g of cellobiose corresponds to 1.1 g of glucose). These results demonstrate the feasibility of producing shikimic acid and its derivatives using an engineered C. glutamicum strain from cellobiose as well as glucose.